2018
DOI: 10.1302/1863-2548.12.180024
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of closed reduction in late-detected hip dislocation: 60 patients aged six to 36 months at diagnosis followed to a mean age of 58 years

Abstract: PurposeThe aims of this study on late-detected developmental dislocation of the hip (DDH) were to assess the outcome in patients aged 55 to 60 years and to define prognostic factors.MethodsThe study included 60 patients (74 hips). Primary treatment was skin traction to obtain closed reduction, followed by hip spica plaster cast. There were 52 girls and eight boys with a mean age at reduction of 19.6 months (8 to 37). Criteria for good long-term outcome were no osteoarthritis (OA) or total hip arthroplasty (THA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Even excluding mild AVN cases (AVN grade 1), our study’s AVN rate is 63.2%, despite performing shortening PFO in 96% of treated joints to lower the acetabulum pressure on the femoral head. Terjesen 33 reported an AVN rate of 8.1% and Thomas et al 35 of 5.7%, while not performing shortening PFO. It might suggest that the natural history of untreated DDH is more responsible for AVN development than excessive femoral head pressure.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Even excluding mild AVN cases (AVN grade 1), our study’s AVN rate is 63.2%, despite performing shortening PFO in 96% of treated joints to lower the acetabulum pressure on the femoral head. Terjesen 33 reported an AVN rate of 8.1% and Thomas et al 35 of 5.7%, while not performing shortening PFO. It might suggest that the natural history of untreated DDH is more responsible for AVN development than excessive femoral head pressure.…”
Section: Discussionmentioning
confidence: 94%
“…To our knowledge, only three studies [33][34][35] have assessed the treatment outcome of DDH patients with comparable follow-up length (Table 4). Our material hips survivorship is worse at 40-years than in Terjesen 33 or Thomas et al's 34 studies by 32% and 23%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, RAD is the most common complication of DDH closed reduction treatment. A prospective multicenter study conducted by Sankar et al ( 2 ) found that even with stable closed reduction, approximately 11% of children still had residual dysplasia, and long-term follow-up results of a study by Terjesen ( 3 ) noted a higher statistic of up to 38%. RAD is the main cause of osteoarthritis (OA) in young adults ( 4 , 5 ) which often requires total hip replacement (THR).…”
Section: Introductionmentioning
confidence: 99%
“…The longest follow-up in DDH seems to be the study on closed reduction from Norway. 11 In patients aged 1.5 to three years, skin traction to obtain gradual closed reduction resulted in 76% survival at patient age 50 years and 54% survival at 58 years. This indicates that gradual reduction by traction, although the method has largely been abandoned, has similar long-term outcome as open reduction combined with Salter osteotomy.…”
mentioning
confidence: 99%